2015
DOI: 10.1590/1678-457x.6722
|View full text |Cite
|
Sign up to set email alerts
|

Several techniques for the preparation of flour from carcasses of the Pantanal alligator (Caiman crocodilus yacare)

Abstract: Flour prepared via current assay methodologies from the carcasses of the Pantanal alligator (Caiman crocodilus yacare) was analyzed for its chemical composition, minerals, fatty acids, and sensorial profile. Carcasses of the Pantanal alligator, originating from the Coocrijapan scientific zoo, Cáceres MT Brazil, were utilized. The carcasses were cooked for 60 minutes in a pressure cooker with water containing 2% salt and 5% chimichurri. The cooked carcasses were then ground and the mass was used for the manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
(26 reference statements)
2
6
0
Order By: Relevance
“…The lipid content was 3.34% for T1, 5.36% for T2, and 1.69% for T3, with a significant difference between all treatments (p<0.05) (Table 2). Lipid contents around 3.94% were obtained elsewhere for yacare carcasses (Fernandes et al, 2015). Despite the difference between treatments, the lipid content of the cooked sausages was quite similar to that obtained for yacare meat.…”
Section: Proximate Compositionsupporting
confidence: 73%
See 1 more Smart Citation
“…The lipid content was 3.34% for T1, 5.36% for T2, and 1.69% for T3, with a significant difference between all treatments (p<0.05) (Table 2). Lipid contents around 3.94% were obtained elsewhere for yacare carcasses (Fernandes et al, 2015). Despite the difference between treatments, the lipid content of the cooked sausages was quite similar to that obtained for yacare meat.…”
Section: Proximate Compositionsupporting
confidence: 73%
“…Carbohydrates were obtained by difference, and amounted to 0.58, 2.65, and 8.51% for T1, T2, and T3, respectively. The contribution of carbohydrates from the yacare tissue is minimum (0.07%) (Fernandes et al, 2015). Thus, variations in carbohydrate contents are also related to the sausage composition, so T1 contained the lowest amount of carbohydrate, which was likely due to it having the lowest inulin content (1%), while more carbohydrate was found in T2 (2% inulin) and T3 (3% inulin), explained by the addition of greater amounts of oligosaccharide inulin, i.e., the more inulin added, the greater the carbohydrate content.…”
Section: Proximate Compositionmentioning
confidence: 99%
“…Again, for comparisons, it presents the 3.67% lipid content reported for yacare meat sausages added of pork fat (Fernandes et al, 2013) and the 1.69-5.36% range obtained for yacare meat-based sausages (Cavenaghi-Altemio et al, 2021). All these values are close to the average lipid content of 3.94% obtained elsewhere for yacare carcasses (Fernandes et al, 2015).…”
Section: Proximate Compositionsupporting
confidence: 72%
“…Finally, the carbohydrate content observed by difference for T1, T2, and T3 was 2.07, 4.11, and 4.42%, respectively (Table 2), with the cassava starch and the sugars the ingredients that mainly contributed to it. The contribution of carbohydrates from the yacare itself is irrisory (0.07%) (Fernandes et al, 2015). Another study reported carbohydrates ranging from 0.58 to 8.51% in yacare sausages.…”
Section: Proximate Compositionmentioning
confidence: 96%
See 1 more Smart Citation